Effects of perceived stress on turnover intention of female healthcare staff: a serial multiple mediation model - Dongling Yuan; Muli Hu; Na Yao; Huiyuan Zhong; Yinghong Xiao; Xiao Zhou; Ruoyi Zhang; Yi Zhang (BMC, 2024)
Abstract Background Healthcare staff in China, especially females, work in a high-pressure, high-load, and high-risk environment, which affects the physical and mental health, the efficiency and quality of work, and increases turnover intention. The present study investigated the relationship between perceived stress and turnover intention in female healthcare staff, and the effects of future-oriented coping and work-family balance on this relationship. Methods Four hundred thirty-five female medical workers were recruited to perform a perceived stress scale, future-oriented coping inventory, work-family balance scale and turnover intention scale. Meanwhile, serial multiple mediation analysis was performed using PROCESS. Results 1) Perceived stress positively predicted the level of turnover intention in female healthcare staff; 2) Preventive coping and proactive coping showed mediation effects on the relationship between perceived stress and turnover intention, and preventive coping positively related to proactive coping; 3) The work-family balance also showed mediation effects on the relationship between perceived stress and turnover intention; 4) Preventive coping, proactive coping and work-family balance showed a serial multiple mediation on the relationship between perceived stress and turnover intention in female healthcare workers. Conclusions Perceived stress affects the level of turnover intention in female healthcare staff through preventive coping, proactive coping, and work-family balance. In addition, the sequential model of future-oriented coping was validated among female healthcare staff.